Efficient synthesis of novel disubstituted pyrido[3, 4-b]pyrazines for the design of protein kinase inhibitors. Issue 2 (25th November 2015) - Antoine, Maud; Schuster, Tilmann; Seipelt, Irene; Aicher, Babette; Teifel, Michael; Günther, Eckhard; Gerlach, Matthias; Marchand, Pascal
Abstract : Urea and aniline derivatives were active at low micromomolar IC50 values against a panel of seven cancer-related protein kinases. Abstract : A novel family of disubstituted pyrido[3, 4- b ]pyrazine-based compounds was discovered as valuable series for the design of promising protein kinase inhibitors. SAR study allowed the identification of 4-(piperidin-1-yl)aniline moiety as pharmacophoric group, in C-5 or C-8 positions of the pyrido[3, 4- b ]pyrazine ring, for binding to the selected therapeutic targets. Several analogues were active at low micromomolar IC50 values against a panel of seven cancer-related protein kinases providing an excellent starting point for further drug discovery optimization.